1985
DOI: 10.1017/s0003356100027884
|View full text |Cite
|
Sign up to set email alerts
|

Retention of copper in the liver of sheep genetically selected for high and low concentrations of copper in plasma

Abstract: The extent to which genetic selection to change the concentration of copper (Cu) in plasma also affected the retention of Cu in the liver was assessed in three experiments. In each, the concentration of Cu was measured in samples of liver (taken by biopsy) and of plasma from female sheep of lines selected from a Scottish Blackface x Welsh Mountain population (which had previously been interbred for several generations) for high and low plasma Cu levels (high line and low line) and from purebred Scottish Blackf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Findings of Ortolani et al (1993) indicated lower Cu level in parasite infected sheep compared to non-infected ones. Fluctuation/deficiency in serum Cu levels were reported in different age groups and sex (Ishag et al, 2014), genetic and breed varieties (Woolliams et al, 1985), in feed (Suttle, 2010) and those with antagonistic elements like Mo, S and Fe in their diets (Marques et al, 2003). Moreover, certain trace elements like Se have a higher capability for absorption and retention in sheep utilizing concentrate feed compared to forage (Koening et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Findings of Ortolani et al (1993) indicated lower Cu level in parasite infected sheep compared to non-infected ones. Fluctuation/deficiency in serum Cu levels were reported in different age groups and sex (Ishag et al, 2014), genetic and breed varieties (Woolliams et al, 1985), in feed (Suttle, 2010) and those with antagonistic elements like Mo, S and Fe in their diets (Marques et al, 2003). Moreover, certain trace elements like Se have a higher capability for absorption and retention in sheep utilizing concentrate feed compared to forage (Koening et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…mulation of the trace element (Bertinchamps et al 1966;Suttle et al 1982;Williams 1985). Welsh Mountain sheep are 50% more efficient in absorbing Cu than Scottish Blackface, and this is associated with higher plasma Cu levels and a greater retention of Cu in the liver (Woolliams et al 1983;Woolliams et al 1985). On the other hand, there appears to be little control over the amounts of Se absorbed, as blood and tissue Se levels reflect the intake of Se.…”
Section: A Absorptionmentioning
confidence: 99%
“…Liver Suttle (1974a,b), Dalgarno and Mills (1975), Suttle and Price (1976), Buckley and Tait (1981) and Woolliams et al (1985) who also found that Cu as copper su$hate was readily absorbed by sheep. In contrast, Ivan and Veira (1985), in a study similar to the present one, showed that copper sulphate supplementation of 6 mg kg-'DM to a corn in AAT activitv (Kelleher and Ivan 1987).…”
Section: Discussionmentioning
confidence: 98%